EKSPERIMENTASI MODEL PEMBELAJARAN THINK-PAIR-SHARE DENGAN MODUL (TPS-M) DITINJAU DARI KECERDASAN INTERPERSONAL - Jatmiko, Jatmiko (Efektor, 2015)
This study is aimed to find out: (1) which one of Think-Pair-Share method with Module (TPS-M), Think-Pair-Share (TPS) or direct learning results better performance; (2) which one of students who have high, medium, or low interpersonal intelligence is better in learning achievement; (3) which one of TPS-M, TPS, or direct learning results better learning achievement on high, medium, and low interpersonal inteligence students. This study used quasi experimental method with 3x3 factorial design. The population was the tenth grade engineering students of vocational school in Nganjuk on academic year 2012/2013. Sampling was stratified cluster random sampling method. The size of sample was 302 students with 101 students in the first experimental class, 105 students in the second experimental class and 96 students in the control class. A questionnaire interpersonal intelligence and achievement tests on mathematics were used to collect the data. The trial of questionnaire instrument includes content validity, internal consistency and reliability. Test trials include content validity, level of difficulty, different power and the reliability. The prerequisite of ANAVA test was normality test using Lilliefors test and the test of homogeneity used the Bartlett test. Balance test used one way analysis of variance with unbalanced cells. Hypothesis testing used two ways analysis of variance with unbalanced cells. Based on the data analysis, it concluded as follows. (1) TPS-M produces better learning achievement than TPS and direct teaching model. TPS learning model provides better learning achievement than the direct instructional model; (2) High interpersonal intelligence students have better mathematics learning outcomes than medium and low interpersonal intelligence students. Medium interpersonal intelligence students have better mathematics learning outcomes than low interpersonal intelligence students. (3) In each high, medium, and low interpersonal intelligence students have better learning achievement in learning model TPS-M than TPS and direct instructional model; furthermore, the high, medium, and low interpersonal intelligence students have better learning achievement in learning model TPS than direct instructional. Keywords: Think-Pair-Share, Module, Interpersonal Intelligence, Mathematics Learning Achievement